Provisions for amphetamine type stimulant users in European prisons - Decorte, Tom (Schriftenreihe "Gesundheitsförderung im Justizvollzug", 2006)
Stimulants use does occur in prisons. These substances are injected, snorted, inhaled or swallowed, though the pattern of use for these substances may be irregular or even occasional. The concepts or categories of the pure 'cocaine user' and the pure 'heroin user' loose part of their usefulness, as the phenomenon of poly drug use is widespread, and changes in the type of substance taken may occur as people enter prison and later again, as they re-enter society. The heroin-oriented strategies do not fit stimulant users and there is a clear need for strategies that surpass the basic medical or product-oriented approach. More than the need for medication, many prisoners express the need for more psychosocial services and options to talk about the psychological dependence, and the psychosocial aspects of their drug taking behaviour. The study was conducted in Belgium, Czech Republic, Ireland, Lithuania, Malta (distant data collection), The Netherlands, Portugal, Slovenia and Sweden and warns that as cocaine and Amphetamine Type Stimulants have become more available and/or more popular among certain segments of the general population, an increase of stimulants use in prisons is likely. <engl.>